Advancing Fault Diagnosis in BLDC Motors: Surge Test-Based Diagnostic Equipment for Phase to Ground Faults - Stephen Larigaduelle; Jeseph Patrick William (Vertex, 2023)
This research introduces a groundbreaking approach to fault diagnosis in Brushless DC (BLDC) motors through the design and validation of specialized diagnostic equipment utilizing surge tests for phase to ground faults. The study focuses on identifying, localizing, and classifying various fault types, including insulation breakdowns, erosion, penetration, and partial grounding within BLDC motors. The research methodology encompasses theoretical frameworks, experimental validations, and comparative analyses with existing diagnostic methods. Surge tests conducted on BLDC motors with induced faults revealed distinct fault signatures, providing precise fault localization and aiding in the establishment of diagnostic criteria and thresholds. The findings showcased the developed equipment's precision, reliability, and automated fault classification capabilities, surpassing the limitations of traditional diagnostic methods. Comparisons with conventional techniques highlighted the advantages of the developed approach, emphasizing its heightened sensitivity, objectivity, and potential for predictive maintenance strategies. The equipment's ability to offer quantifiable fault parameters and establish diagnostic thresholds presents a transformative potential for proactive maintenance, minimizing downtime, and enhancing operational efficiency in BLDC motor-driven systems. The research findings underline the significance of surge tests and specialized diagnostic equipment in revolutionizing fault diagnosis practices for BLDC motors. The implications extend to industry-wide adoption, offering a pathway for enhanced reliability, safety, and operational continuity in various industrial applications.